Comparative Analysis of the Marriage Age Dispensation in Islamic Family Law in Indonesia and Algeria - Ibnu Amin; Nurus Shalihin; M Sholihin; YS Tenra Septu Amin; Lendrawati Lendrawati (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2026)
This study aims to analyze comparatively the legal policy regarding the granting of marriage dispensation in the Islamic family law system in two Muslim-majority countries, namely Indonesia and Algeria. The focus of the study is directed at how regulations in each country regulate the age limit for marriage and the mechanism for granting marriage age dispensations, as well as how these norms are rooted in the principles of Islamic law that are influenced by the national legal structure. This research uses a qualitative method with a normative juridical approach and comparative legal analysis, through an examination of laws, implementing regulations, official state documents and classical and contemporary Islamic legal literature. The results of the study show that Indonesia through Law Number 1 of 1974 in conjunction with Law Number 16 of 2019 sets the age of marriage of 19 years for men and women, but still opens up dispensation space through the judicial channels as stipulated in Supreme Court Regulation Number 5 of 2019. Algeria in the revised Code de la Famille in 2005 sets a minimum age of 19 years without distinction between sex, with the granting of a more administrative dispensation governed by the civil courts, but giving judges broader authority to give consideration to their verdicts without more specific technical instructions. Both countries use the principle of benefit as a normative justification, but differences in social, political and legal contexts make the implementation of marriage practiced in different frameworks. The conclusion of this study is that the legal formulation of marriage dispensation in Indonesia and Algeria reflects legal ijtihad efforts that are adaptive to changing times, but still require social control and protection of children's rights within the framework of justice and benefit values.Penelitian ini bertujuan untuk menganalisis secara komparatif kebijakan hukum mengenai pemberian dispensasi nikah dalam sistem hukum keluarga Islam di dua negara berpenduduk mayoritas Muslim, yakni Indonesia dan Aljazair. Fokus kajian diarahkan pada bagaimana regulasi di masing-masing negara mengatur batas usia perkawinan dan mekanisme pemberian dispensasi usia nikah, serta bagaimana norma tersebut berakar pada prinsip-prinsip hukum Islam yang dipengaruhi oleh struktur hukum nasional. Penelitian ini menggunakan metode kualitatif dengan pendekatan yuridis normatif dan perbandingan hukum (comparative legal analysis), melalui telaah terhadap undang-undang, peraturan pelaksana, dokumen resmi negara serta literatur hukum Islam klasik dan kontemporer. Hasil penelitian menunjukkan bahwa perbedaan utama Indonesia dan Aljazair dalam dispensasi nikah terletak pada mekanisme peradilan, ruang diskresi hakim, dan orientasi perlindungan anak. Indonesia melalui Undang-Undang Nomor 1 Tahun 1974 jo Undang-Undang Nomor 16 Tahun 2019 menetapkan usia menikah 19 tahun serta membuka dispensasi melalui mekanisme yudisial yang diatur rinci dalam Peraturan Mahkamah Agung Nomor 5 Tahun 2019. Regulasi ini menekankan kepentingan terbaik bagi anak melalui pertimbangan psikologis, kesehatan, pendidikan, dan sosial sehingga diskresi hakim lebih terbatas secara prosedural. Sebaliknya, Aljazair melalui Code de la Famille revisi 2005 juga menetapkan usia minimal 19 tahun, tetapi tanpa pedoman teknis khusus mengenai dispensasi. Akibatnya, hakim memiliki ruang diskresi lebih luas dalam mempertimbangkan alasan sosial, budaya, dan kemaslahatan keluarga. Temuan ini menunjukkan Indonesia lebih berorientasi pada perlindungan anak berbasis regulasi, sedangkan Aljazair menekankan fleksibilitas penafsiran hakim dalam hukum keluarga Islam.